Transitions to Regular Smoking and Nicotine Dependence in the Adolescent National Comorbidity Survey (NCS-A) - Dierker, Lisa (Ann Behav Med, 2012)
OBJECTIVE: This study aims to investigate the occurrence of nicotine dependence following the achievement of previous smoking milestones (initiation, weekly, and daily smoking). METHOD: Analyses are based on data from The National Comorbidity Survey-Adolescent, a nationally representative face-to-face survey of 10,123 adolescents (age 13–17) conducted between 2001 and 2004. RESULTS: Among adolescents who had ever smoked (36.0%), 40.7% reached weekly smoking levels and 32.8% had reached daily smoking. Approximately one in five adolescents who had ever smoked (19.6%) met criteria for nicotine dependence. An earlier age of smoking initiation, a shorter time since the onset of smoking and faster transitions among smoking milestones were independently associated with the onset of daily smoking and nicotine dependence. CONCLUSIONS: These findings shed new light on the course of smoking and nicotine dependence during adolescence by demonstrating a rapid transition across smoking stages for those most at risk for the development of chronic and dependent use.